2020
DOI: 10.1007/s40964-020-00121-x
|View full text |Cite
|
Sign up to set email alerts
|

Laser powder bed fusion of 30CrNiMo8 steel for quenching and tempering: examination of the processability and mechanical properties

Abstract: The layer-by-layer principle of additive manufacturing technology laser powder bed fusion (LPBF) opens up completely new possibilities in the design and manufacturing of lightweight and efficient gear components. For example, integration of contour conform cooling and lubrication channels into gear components can increase their service life and reduce lubricant consumption. Steels for quenching and tempering and case hardening steels are commonly used materials for gear components. However, the availability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
(21 reference statements)
2
17
0
Order By: Relevance
“…Additionally, the elongation at break of 14.2-16.9% (quenched and tempered) is in line with values presented in the relevant literature [25,26]. The notch impact tests revealed remarkably high impact energies of 99-109 J for the LPBF-processed 30CrNiMo8 in the quenched and tempered states compared to the bulk material [25], indicating high ductility.…”
Section: Manufacturingsupporting
confidence: 88%
See 3 more Smart Citations
“…Additionally, the elongation at break of 14.2-16.9% (quenched and tempered) is in line with values presented in the relevant literature [25,26]. The notch impact tests revealed remarkably high impact energies of 99-109 J for the LPBF-processed 30CrNiMo8 in the quenched and tempered states compared to the bulk material [25], indicating high ductility.…”
Section: Manufacturingsupporting
confidence: 88%
“…A previous study revealed promising mechanical properties of the 30CrNiMo8 and a high relative when processed with LPBF [25]. The yield strength and tensile strength of the quenched and tempered specimens were 1009-1016 MPa and 1094-1098 MPa [25], respectively, which are comparable with the bulk material with a similar heat treatment [25,26]. Additionally, the elongation at break of 14.2-16.9% (quenched and tempered) is in line with values presented in the relevant literature [25,26].…”
Section: Manufacturingmentioning
confidence: 97%
See 2 more Smart Citations
“…The point distance corresponds to the distance between each of the laser's exposure points, whereas the exposure time defines the duration of the laser exposure. The input volume energy density E V (2) is a function of the laser power P L , scan velocity v s , layer thickness l z , and hatch spacing h s [3].…”
Section: Laser Powder Bed Fusionmentioning
confidence: 99%